Different pattern of risk factors for post-ERCP pancreatitis in patients with biliary stricture. (4th May 2018) - Zheng, Liang; Wang, Xiangping; Tao, Qin; Liang, Shuhui; Wang, Biaoluo; Luo, Hui; Zhang, Rongchun; Zheng, Liyue; Yang, Shengye; Chen, Jie; Pan, Yanglin; Guo, Xuegang
Abstract: Objective: To identify possible risk factors associated with post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) in biliary stricture (BS), common bile duct stone (CBDS) and unselected patients. Materials and methods: Consecutive ERCP patients with native papilla from January 2010 to December 2014 in Xijing Hospital were eligible. Patient-related and procedure-related parameters were collected retrospectively. The primary outcome was PEP. Univariate and multivariate logistic regression were used for data analysis. Results: Totally 3133 unselected patients were included. 695 (22.2%) had BS alone and 1893 (60.4%) had CBDS alone. PEP incidence was higher in BS group compared with CBDS group (6.8% vs. 3.8%, p  = .001). Among patient-related factors, duodenal stenosis (OR, 2.74; 95%CI, 1.14–6.59) and hilar stricture (OR, 2.59; 95%CI, 1.41–4.77) were found to be independently associated with PEP in BS group. While female gender (OR, 2.11; 95%CI, 1.20–3.73) and normal total bilirubin (OR, 1.93; 95%CI, 1.13–3.32) were related to PEP in CBDS group. Among procedure-related factors, cannulation time ≥ 5 min (OR, 2.38; 95%CI, 1.06–5.33) and precut (OR, 3.20; 95%CI, 1.35–7.59) was respectively the only independent risk factor for PEP in BS and CBDS group. Conclusions: Patients with BS and CBDS had different patterns of patient-related and procedure-related risk factors for PEP. The prophylaxis of PEP may need to be individualized based on different indications.